2016
DOI: 10.1177/1060028016651279
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Agonists in Type 1 Diabetes Mellitus

Abstract: The use of GLP-1 agonists should be considered in T1DM patients who are overweight or obese and not at glycemic goals despite aggressive insulin therapy; however, tolerability of these agents is a potential concern. Liraglutide has the strongest evidence for use and would be the agent of choice for use in overweight or obese adult patients with uncontrolled T1DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…Several authors have recently reviewed all the available evidence on the use of GLP‐1RAs in patients with T1DM, and exenatide and liraglutide are the only GLP‐1RAs on the market with clinical data in T1DM. Although the studies are limited in number, have small sample sizes and are of short duration, it has been shown that both agents were able to reduce glycated haemoglobin (HbA1c) concentrations, fasting and postprandial glucose concentrations and insulin doses, as well as body weight, without increasing the risk of hypoglycaemia in adult patients with T1DM.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Several authors have recently reviewed all the available evidence on the use of GLP‐1RAs in patients with T1DM, and exenatide and liraglutide are the only GLP‐1RAs on the market with clinical data in T1DM. Although the studies are limited in number, have small sample sizes and are of short duration, it has been shown that both agents were able to reduce glycated haemoglobin (HbA1c) concentrations, fasting and postprandial glucose concentrations and insulin doses, as well as body weight, without increasing the risk of hypoglycaemia in adult patients with T1DM.…”
supporting
confidence: 91%
“…In conclusion, over the last few years, GLP‐1RAs have emerged as important options in the treatment of T2DM, and increasing data support their potential extended use, in combination with insulin, in patients with T1DM . Although the studies to date are limited, the metabolic effects are fairly consistent but the cardiovascular effects may be different and need to be further elucidated.…”
mentioning
confidence: 99%
“…In adults with type 1 diabetes, pramlintide resulted in a decrease in postprandial hyperglycaemia and glucagon, HbA 1c and weight compared with insulin-only therapy [80,81]. Other agents being investigated in type 1 diabetes are thiazolidinediones (TZDs), glucagon-like peptide-1 (GLP-1) agonists and sodium-glucose cotransporter 2 (SGLT2) inhibitors, drugs used in type 2 diabetes [82,83].…”
Section: Treatmentmentioning
confidence: 99%
“…They reduce appetite and slow gastric emptying and thus reduce body weight and body fat by lowering energy intake [ 63 ]. Their use in patients with T1D resulted in significant weight reductions in overweight and obese patients [ 64 ••]. However, improvement in glycemic control did not reach statistical significance in trials using active comparators [ 64 ••].…”
Section: Weight Management In Type 1 Diabetesmentioning
confidence: 99%
“…Their use in patients with T1D resulted in significant weight reductions in overweight and obese patients [ 64 ••]. However, improvement in glycemic control did not reach statistical significance in trials using active comparators [ 64 ••]. Liraglutide, a GLP-1 analog, in conjunction with insulin has been shown to improve glycemic control and induce weight loss in patients with T1D [ 65 , 66 ].…”
Section: Weight Management In Type 1 Diabetesmentioning
confidence: 99%